2015
DOI: 10.3390/ijms16035618
|View full text |Cite
|
Sign up to set email alerts
|

PEDF Improves Cardiac Function in Rats with Acute Myocardial Infarction via Inhibiting Vascular Permeability and Cardiomyocyte Apoptosis

Abstract: Pigment epithelium-derived factor (PEDF) is a pleiotropic gene with anti-inflammatory, antioxidant and anti-angiogenic properties. However, recent reports about the effects of PEDF on cardiomyocytes are controversial, and it is not known whether and how PEDF acts to inhibit hypoxic or ischemic endothelial injury in the heart. In the present study, adult Sprague-Dawley rat models of acute myocardial infarction (AMI) were surgically established. PEDF-small interfering RNA (siRNA)-lentivirus (PEDF-RNAi-LV) or PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Recombinant PEDF-lentivirus (PEDF-LV) was prepared as described previously [15]. PEDF overexpression plasmids and the RNAi vector were packaged in 293T cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant PEDF-lentivirus (PEDF-LV) was prepared as described previously [15]. PEDF overexpression plasmids and the RNAi vector were packaged in 293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…It is expressed in multiple tissues and exerts diverse physiological activities, for instance blocking angiogenesis and tumor growth, anti-inflammatory and anti-oxidation [12,13,14]. Our previous studies have declared that PEDF inhibits left ventricular remodeling and improves cardiac function in rats with acute myocardial infarction, and PEDF protects against hypoxia-induced apoptosis and necroptosis via an anti-oxidative effect [15,16]. However, it is not known whether PEDF inhibits the activation of the NLRP3 inflammasome to protect against myocardial cell death in hypoxia cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . demonstrated that cardiomyocyte apoptosis dominantly contributed to myocardial infarction, by reducing which pigment epithelium‐derived factor managed to prevent cardiac ischaemic injury . Furthermore, autophagy has been regarded as a causative factor for AMI.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have demonstrated that cardiomyocyte apoptosis takes place in heart samples from patients suffering from MI [2]. Inhibition of cardiomyocyte apoptosis MI-induced can lead to a decrease of the infarct size and an improvement of cardiac function [3][4][5]. Cardiac shock wave therapy (CSWT) is a novel approach that provides a new choice for severe CHD.…”
Section: Introductionmentioning
confidence: 99%